Study of psi(2S) production and cold nuclear matter effects in pPb collisions at root s(NN)=5 TeV - Aaij, Roel; Beteta, C. Abellan; Adeva, B.; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; et al. (Journal of high energy physics, 2016)
The production of ψ(2S) mesons is studied in dimuon final states using proton-lead (pPb) collision data collected by the LHCb detector. The data sample corresponds to an integrated luminosity of 1.6 nb−1. The nucleon-nucleon centre-of-mass energy of the pPb collisions is √sNN=5 TeV. The measurement is performed using ψ(2S) mesons with transverse momentum less than 14 GeV/c and rapidity y in the ranges 1.5 < y < 4.0 and −5.0 < y < −2.5 in the nucleon-nucleon centre-of-mass system. The forward-backward production ratio and the nuclear modification factor are determined for ψ(2S) mesons. Using the production cross-section results of ψ(2S) and J/ψ mesons from b-hadron decays, the bb¯¯ cross-section in pPb collisions at √sNN=5 TeV is obtained.
*The LHCb collaboration: R. Aaij, P. D'Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, U. Uwer, M. Vesterinen, A. Zhelezov [und 519 weitere Personen]
Im Titel ist "psi" als griechischer Buchstabe dargestellt
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 17.07.2020